2021
DOI: 10.1016/j.drugalcdep.2021.108938
|View full text |Cite
|
Sign up to set email alerts
|

Has the increased participation in the national campaign ‘Dry January’ been associated with cutting down alcohol consumption in England?

Abstract: Highlights Dry January was not associated with large population-level declines in alcohol consumption. People were more likely to cite Detox (e.g., Dry January) as a motive in a quit attempt in January. The proportion of people citing Detox (e.g., Dry January) throughout the year as a reason for a quit attempt increased between 2014 and 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…One of the studies was then excluded because of its experimental research design [ 16 ] as well as five Dry July Annual reports providing no answer to any of the four research questions. Six studies [ 17 22 ] and seven Dry July Annual reports [ 23 – 29 ] were finally included for the review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One of the studies was then excluded because of its experimental research design [ 16 ] as well as five Dry July Annual reports providing no answer to any of the four research questions. Six studies [ 17 22 ] and seven Dry July Annual reports [ 23 – 29 ] were finally included for the review (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). The six studies were published between 2016 and 2021, five of them referred to Dry January [ 17 20 , 22 ], and one pertained to Febfast 2012 [ 21 ]. Characteristics of the reviewed studies and reports can be found in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations